History of Primary Health Care in Peru: understanding its path and current perspectives - Llanos Zavalaga, Luis Fernando (2021)
The development of primary health care in Peru has achieved important milestones in its history. The social foundations that were formed in the health services in the previous century can be explained by events during the colonial era. Furthermore, after the Declaration of Alma-Ata in 1978, Peru faced several obstacles that further polarized the population from different economic strata. However, the Ministry of Health, together with international cooperation, began to develop health programs with the objective of providing primary care to the population, with the fundamental results that will help to unify the population and be one-step closer to achieving universal health care coverage. Therefore, in this document, we describe the events leading to Peru’s current health system, the achievements of Primary Health Care services, and the use of technological devices to improve public health.